Workplace Flexibility Research 2015-2020: A Challenge for Future Research - Helmiatin, Helmiatin; Sawitri, Hunik Sri Runing; Vu, Nguyen Thanh (Universitas Muhammadiyah Magelang, 2022)
This article provides a literature review of workplace flexibility from several fields of research. This research was conducted based on a systematic review of workplace flexibility, from 31 articles carried from the Publish or perish database, open knowledge map, and VOS viewer as well as from Science Direct and Emerald science from 2015 to 2021. Based on the results of some keywords, several variables studied include employee engagement, gender, job satisfaction, work-family conflict, communication, and technology. This study's results are a conceptual model and future research developments. There is a holistic perspective in defining workplace flexibility, and this broader definition needs to be embedded in the context bigger than organizational culture change. Flexibility can act as an independent, mediation, moderation, or dependent variable in various relationships with other variables. Most studies use quantitative methods, and several studies are using a qualitative approach. This study intends to represent the knowledge of workplace flexibility concept for further research, as for practitioner is as guidelines to formulate and promote the implementation of workplace flexibility. The research limited only based on 31 articles in the last five years.